CONGKLAK APLICATION TO INCREASE UNDERSTANDING THE CONCEPT OF ROUND NUMBERS IN ELEMENTARY SCHOOLS - Nur Sad Utami; Sri Utaminingsih; Santoso Santoso (Universitas Muria Kudus, 2021)
The purpose of this study was to determine students' understanding of integer concepts through innovative learning media.The method used in this research is Research and Development (R and D) research to produce a product.The Congklak application is designed by incorporating the traditional congklak game. This research was conducted at SD Negeri Sayung 1, Sayung District, Demak Regency. The product is designed through learning integer material using the context of the congklak game. The research stage consists of information gathering, planning, product development and product validation.The results of this study indicate that the Congklak application (Congklak.App) can be used to improve understanding of the integer concept. This is supported by the results of teacher and student responses as well as the results of the validation of experts showing very good criteria and suitable for use in learning integer concepts in elementary schools.